Sistem Pelapisan Sosial Dalam Ritual Teing Ela Tinu pada Masyarakat Desa Watu Rambung - Apolonia Mulya; I Gusti Putu Sudiarna (Department of Anthropology Udayana University, 2019)
Watu Rambung Village is one of the villages in South Lembor District, West Manggarai Regency, which has a sacred ritual and is still preserved by the people of Watu Rambung Village. The ritual is called the Teing Ela Tinu ritual. The Teing Ela Tinu Ritual is a traditional event conducted by children as a form of appreciation and retribution to their parents. This ritual is performed when the children are married or have their own lives.The formulation of the problems in this study include (1) How the social coating system in the Ela Tinu Teing Ritual (2) The process of implementing the Ela Tinu Teing Ritual. This study aims to determine the social coating system in the Teing Ela Tinu ritual, as well as to know the process of implementing the Ela Tinu Teing Ritual in Watu Rambung Village. This research uses the theory of Bronislaw Malinowski about structural functional. The method used is a qualitative research method. Data collection techniques include observation, interviews, and literature study. The analysis used is descriptive qualitative.